(untitled) (Proceedings of the International Conference on Public Health, 2017)
Obesity in relation to Sugar Sweetened Beverages (SSB) consumption, a worldwide problem has extensively documented in western countries. Still, Indian data on SSB consumption of adolescents is lacking. Therefore, nutritional assessment, SSB intake, dietary consumption and milk consumption (assessed through 24 hour dietary recall method) prevalence, locale of SSB (assessed through semi structured questionnaire) among adolescents was recorded. Study was conducted at private schools of Jodhpur city (Rajasthan, India) including (600) adolescent aged 13-15 years. Grading of nutritional status was compared with WHO (2007) classification .For selection of categories and classification of SSB’S, NHANES III and NHANES 1999-2004 was referred. Among 15 years obese (20.62%) boys and (24.60%) girls were consuming maximum dietary calories (i.e. 1887.5±67.17 k.cal/day vs. 1942.16±296.94 k.cal/day respectively). Prevalence of soft drink consumption on a daily basis was reported among all the age group (100%) adolescents. Most preferred place for SSB consumption was home and school. Girls aged 15 years, consumed lesser milk (165.49±128.34 ml/day) as compared to boys. With advancing age, the caloric intake from SSB has increased among adolescents.